2021
DOI: 10.1111/ijcp.14272
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lens capsular tension ring on preventing capsular contraction syndrome in the surgery of retinitis pigmentosa combined with cataract: Retrospective case series

Abstract: Retinitis pigmentosa (RP) is a clinically common congenital retinal disease, with an incidence of about 1/4000. 1 The pathological manifestations include progressive dysfunction of retinal pigment epithelial cell and photoreceptor cell, and patients tend to be night blind and have reduced vision field and poor vision. Currently, there is no effective treatment or prevention measures for RP, and interventions such as stem cell transplantation and gene therapy are still in the research stage. 2,3 In addition to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…One Chinese article [13] was excluded because of insufficient data (no duration of follow-up) and two English articles were excluded because the results had been repeatedly reported by the same research group [14,15]. The remaining 16 studies [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] were included for data analysis. The flowchart of the selection process is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One Chinese article [13] was excluded because of insufficient data (no duration of follow-up) and two English articles were excluded because the results had been repeatedly reported by the same research group [14,15]. The remaining 16 studies [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] were included for data analysis. The flowchart of the selection process is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This helps to maintain the effective position and stability of the IOL, improve higher-order aberrations, and enhance visual quality ( 91 ). Therefore, we recommend the intraoperative implantation of CTR for cataract patients who have risk factors, as a preventive measure against postoperative ACCS ( 30 , 92 ). For instance, a retrospective study conducted on patients undergoing cataract surgery with RP revealed that the incidence of ACCS was lower in those who received CTR implantation compared to those without CTR ( 93 ).…”
Section: Interventions For Accsmentioning
confidence: 99%
“…Furthermore, higher rates of posterior capsular opacification and anterior capsule phimosis have been described following cataract surgery in patients with RP, which may also negatively influence visual outcomes if left untreated [ 178 ]. Despite the challenges regarding cataract surgery in RP, several studies have demonstrated its benefit, showing average BCVA improvements between studies ( Table 1 ) [ 105 , 162 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 ]. Subjectively, visual improvement was reported in 44.8–96.7% of patients included in these studies [ 177 ].…”
Section: Management Of Rp-associated Complicationsmentioning
confidence: 99%
“…Large capsulorrhexis can assist with optimal maneuvering, while also reducing the risk of capsular phimosis. The use of a capsular tension ring may also provide stability and decrease the risk of IOL (sub)luxation and anterior capsular phimosis, although the insertion itself of the capsular tension ring may also cause strain on the lens zonule system, so prophylactic insertion of such a ring may not be indicated [ 177 , 182 ]. IOL (sub)luxation at short- or long-term follow-up in RP has been reported in several case studies, and these cases were managed using scleral suture fixation or by replacing them with a range of anterior chamber IOLs after the (sub)luxated IOL had been removed, often requiring accompanying vitrectomy [ 191 , 192 , 193 ].…”
Section: Management Of Rp-associated Complicationsmentioning
confidence: 99%